Growth And Characterization Of Pd/Sio2/Zno Nanorods For Electrically Pumped Random Laser - Ooi, Kevin Zheng (2023)
ZnO appeared to be a promising semiconductor material in optical devices, transparent ohmic contacts, transparent thin film and heterostructure transistors, chemical/bio sensors, and piezotransducers owing to its properties such as high exciton binding energy and large direct band gap. Many research papers have been generated based on the studies of ZnO due to its ability to grow as different type of nanostructures. ZnO nanostructures can be prepared in many different shapes by customizing the growth parameters. ZnO nanorods has been chosen to be the research target in this work owing to its high surface to volume ratio, and simplicity to fabricate. Among all the growth techniques, Chemical Bath Deposition (CBD) stand out to be an easy and low cost technique.